Closure to Discussion by K. Prakash and A. Sridharan of Atterberg limits and remolded shear strength water content relationships [Geotechnical Testing Journal, Vol. 36, No. 6, pp. 939 947] - O'Kelly, Brendan C. (My University, 2014)
This article presents the closure to the discussion on the Geotechnical Testing Journal, GTJ20130012 , Vol. 36, No. 6, which had three stated objectives : (i) a critical assessment of empirical methods for predicting remolded undrained strength (s ur ) at different water contents on the basis of measured Atterberg limit value s; (ii) a review of s ur values mobilized at the Casagrande liquid limit ( LL) and plastic limit ( PL) conditions and hence the strength variation over the plas tic range; and (iii) a new approach was propose for predicting s ur values mobilized at different water contents. The original article stated the importance of clay mineralogy on clay behavior . A referenced comment was made regarding discourse by other researchers in recent literature on the link between mineralogy and differences in strengths at LL determined using the Casagrande cup and fall cone approaches. A lthough outside the immediate scope of the original article, this closure presents th e opportunity to elaborate on this discourse since specifically raised by the discussers . The discussers also raised an unrelated but important point, namely attempts by several researchers of late to determine the PL using variants of the fall cone method . The author concurs with the discussers that these approaches deduce a strength - related reference water content that is fundamentally different from the lower water content limit for soil workability, which the Casagrande PL can be considered
PUBLISHED
Keywords: Atterberg limits; clay; fall cone; mineralogy; shear strength; Geotechnics